The behavioral and physiological effects of high‐fat diet and alcohol consumption: Sex differences in C57BL6/J mice. Issue 6 (20th April 2017) - Gelineau, Rachel R.; Arruda, Nicole L.; Hicks, Jasmin A.; Monteiro De Pina, Isabella; Hatzidis, Aikaterini; Seggio, Joseph A.
Abstract: Background and Objective: Animal studies can be a great tool to investigate sex differences in a variety of different ways, including behavioral and physiological responses to drug treatments and different "lifestyle variables" such as diets. Consumption of both high‐fat diets and alcohol is known to affect anxiety behaviors and overall health. This project investigated how high‐fat diet and alcohol access and its combination affected the behavior and physiology of male and female C57BL/6J mice. Method: Mice were separated into three food groups: high‐fat diet, 10% fat diet, and regular chow, and each group was paired with either water or 10% alcohol. Behavioral assays included diet and alcohol preference, light‐dark box, open field, and feeding and drinking measurements. Physiological measures included glucose tolerance tests and measurement of brain‐derived neurotrophic factor, insulin, and leptin levels. Results: Females and males differed in the open field, as male mice decreased activity, while females increased activity when consuming high‐fat diet. While females consumed more ethanol than males, alcohol consumption was able to improve glucose tolerance and increase anxiety in both sexes. Lastly, females were more resistant to the physiological changes caused by high‐fat diet than males, as females consuming high‐fat diet exhibited decreased insulin secretion, less change to brain‐derived neurotrophic factor levels, and better glucose tolerance than males consuming high‐fat diet. Conclusion: These results suggest that the response to high‐fat diet and alcohol consumption is sex dependent and that males are more affected both behaviorally and physiologically by high‐fat diet compared to females. Abstract : Sex differences in C57BL6/J mice were observed for both behavior and overall health when consuming high‐fat diet and alcohol. Female mice were more resistant to changes in behavior and health when consuming high‐fat diet as they exhibited reduced body weight gain, reduced insulin levels, and had increased locomotion in the open field compared to males. While female mice consumed more ethanol, ethanol was able to equally improve glucose tolerance and worsen anxiety in both sexes.